Broad ligament fibroid-a diagnostic and surgical challenge - Thanigachalam, Kunthavvai; Natarajan, Usha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Broad ligament fibroids, a rare subset of uterine leiomyomas, present unique diagnostic and surgical challenges due to their extrauterine location and potential to mimic adnexal masses. We present two illustrative cases: a 37-year-old parous woman with early satiety and abdominal pain found to have a 25×20 cm pseudo-broad ligament fibroid extending to the right lumbar region, successfully managed with ureteric catheterization and open enucleation; and a 50-year-old parous woman with abdominal pain from a 27×15×5 cm fibroid, treated via TAH+BSO with preoperative stenting. These cases highlight the diagnostic dilemmas posed by broad ligament fibroids, the indispensable role of MRI in surgical planning, and the importance of tailored approaches ranging from fertility-sparing techniques to definitive surgery. Both instances underscore the necessity of meticulous preoperative preparation, including ureteral protection strategies, and demonstrate how individualized management based on patient age, symptoms, and reproductive goals can lead to successful outcomes despite the anatomical challenges inherent to these rare tumors.